A hydrodynamic approach to non-equilibrium conformal field theories. (2nd March 2016) - Bernard, Denis; Doyon, Benjamin
Abstract: We develop a hydrodynamic approach to non-equilibrium conformal field theory. We study non-equilibrium steady states in the context of one-dimensional conformal field theory perturbed by the irrelevant operator. By direct quantum computation, we show, to first order in the coupling, that a relativistic hydrodynamic emerges, which is a simple modification of one-dimensional conformal fluids. We show that it describes the steady state and its approach, and we provide the main characteristics of the steady state, which lies between two shock waves. The velocities of these shocks are modified by the perturbation and equal the sound velocities of the asymptotic baths. Pushing this approach further, we are led to conjecture that the approach to the steady state is generically controlled by the power law t −1/2, and that the widths of the shocks increase with time according to t 1/3 .